Genetic and genomic studies of production, composition, and processability characteristics of milk from dairy sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Manawatū, New Zealand - Marshall, Ana Carolina (Massey University, 2024)
The main objective of this study was to perform genetic and genomic studies of sheep milk production, composition, and processability, particularly concerning cheese-making aptitude (milk coagulation properties) of sheep milk. The milk traits were investigated in a flock of 169 lactating ewes producing on a pasture-based system in Masterton, New Zealand. The total yield during the 2021-2022 season was 86.1 kg/ewe in 130 days of milking after the suckling period. The effects of animal factors on the lactation curves, and on milk composition and processability (milk coagulation properties, individual laboratory cheese yield, and heat coagulation time) throughout the season were investigated and discussed. Stage of lactation significantly (p < 0.05) influenced processability. In late lactation, the rennet coagulation time was longer, the curd at 30 minutes after rennet addition was softer, and milk heat stability was lower. In addition, milk protein polymorphisms were shown to influence milk composition and protein composition. Particularly, heat stability was affected by β-lactoglobulin polymorphism. The milk processability traits were also significantly associated with protein composition. The heritability estimates for milk production, composition, and processability traits ranged from 0.12 to 0.48. The genetic correlations obtained indicate that genetic improvement of this flock for higher yields of fat, and protein, and for lower somatic cell score, should indirectly improve milk coagulation traits in this flock. However, other traits such as milk pH, percentage traits (protein, casein, and lactose percentages), ratio of casein to protein, calcium, and ratio of casein to calcium were more strongly correlated with processability. The genome-wide association study performed on 149 dairy sheep genotyped with 50K SNPs Bead Chips, revealed a total of 87 SNPs and 55 candidate genes across Ovis aries autosomes 2, 3, 6, 16, 18, 20, 25, and 26. The genetic architecture of milk coagulation traits was similar to that of the ratio of casein to calcium, pH, lactose, and the ratio of casein to protein. The genetic correlations and identification of potential genes associated with the control of these milk traits provide valuable insights for the selection of superior dairy sheep in New Zealand. The findings of this thesis need to be validated with a systematic large-scale recording scheme before developing a selection index for dairy sheep populations in New Zealand.
Keywords: dairy sheep, milk production, milk composition, milk processability, milk coagulation properties, genetics, genome-wide association; 300302 Animal management; 310509 Genomics